British Military Operations, 1945-1984 - Edited by Pimlott, John (Hamlyn Group Ltd. London, 1983)
Includes material on the Korean War, Suez crisis, NATO, Northern Ireland, and the Falklands War.
Include Illustration, Map and Index
Keywords: Great Britain